Answer:
[tex]y+2=4(x-1)[/tex]
Step-by-step explanation:
we know that
The equation of the line into point-slope form is equal to
[tex]y-y1=m(x-x1)[/tex]
Let
[tex]A(1,-2), B(2,2)[/tex]
Find the slope of the line AB
The formula to calculate the slope between two points is equal to
[tex]m=\frac{y2-y1}{x2-x1}[/tex]
substitute
[tex]m=\frac{2+2}{2-1}[/tex]
[tex]m=\frac{4}{1}[/tex]
[tex]m=4[/tex]
With the point A and the slope m find the equation of the line
[tex]y-(-2)=4(x-1)[/tex]
[tex]y+2=4(x-1)[/tex]